The landscapists redefining landscape relations - Wall, Ed; Wall, Ed (Profile)
Who defines the landscapes around us? What practices are employed as contemporary landscapes are produced? This issue argues that landscapes are made and remade through interrelations between people and the world around them, from geographers investigating the lives of urban wastelands to landscape architects projecting future cities, and from migrants navigating border systems to artists working with local residents. In contrast to tendencies to emphasise the physical forms of landscapes, with their potential to be redesigned and represented in drawings, this issue brings to the forefront the social constructedness of landscapes by focusing on a range of critical practices and daily actions. As conventional frames of landscape are challenged, other ways of measuring, mapping, imagining, designing, building and occupying them are revealed. For centuries, artists and designers have represented landscapes of power in paintings and have transformed them through their design proposals. But in recent years a number of researchers, designers, artists and activists have explored an expanded field of landscape, investigating populations fleeing conflict zones, reimagining cities facing ecological challenges, questioning territorial claims, and critiquing processes of urbanisation. This issue focuses on some of these individuals whose work and livews encompass a diverse range of practices, brought together through their critical redefinition of landscape relations.